EFFECTIVENESS OF THE IMPLEMENTATION OF THE ELIMINATION OF MOTOR VEHICLE TAX FINES IN RIAU PROVINCE IN 2023 AT THE RIAU PROVINCIAL REGIONAL REVENUE AGENCY - Afrinaldi Rustam; Syed Agung Afandi; Marta Hasanah; Jihan Pari Kesid (Yayasan Wayan Marwan Pulungan, 2025)
This study aims to analyze the effectiveness of the implementation of the policy of eliminating motor vehicle tax fines in Riau Province in 2023 implemented by the Riau Province Regional Revenue Agency (Bapenda). This policy on the elimination of motor vehicle tax fines is expected to encourage taxpayers' awareness and compliance in fulfilling their obligations, as well as increase regional revenue from the tax sector. In addition, this policy is implemented as a step to reduce the economic burden of the community after the COVID-19 pandemic. The research method used is a descriptive qualitative approach with data collection through interviews, observations, and documentation at the Riau Provincial Bapenda. This study also examines quantitative data related to the increase in motor vehicle tax revenue during the period of fine elimination. The results of the study show that the implementation of the policy of eliminating motor vehicle tax fines is effective in increasing taxpayer awareness and contributing to increasing regional revenue. However, there are several challenges such as a lack of even socialization and technical difficulties in managing tax administration. To achieve more optimal results, it is necessary to improve coordination between related institutions and a more comprehensive communication strategy to the community. The conclusion of this study is that the policy of eliminating motor vehicle tax fines in Riau Province in 2023 has proven to be effective in increasing taxpayer participation and regional revenue, but it needs to be accompanied by improvement measures in socialization and administrative management to achieve sustainability.